2016
DOI: 10.1002/wcc.400
|View full text |Cite
|
Sign up to set email alerts
|

Visual climate change art 2005–2015: discourse and practice

Abstract: During the last decade (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015), artists from all over the world have taken on climate change as the subject matter of their work. Encouraged by activists (most notably Bill McKibben), artists have appropriated climate change as a social problem and decided that they too, alongside journalists, scientists, and activists, were called upon to engage with this issue. Dozens of noteworthy exhibitions, most notably in Boulder (2007) (2015), have placed clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 40 publications
2
43
0
1
Order By: Relevance
“…The past few decades have witnessed artists using images, installations and experiences to communicate about the environment and climate change, with a growing number of eco-Art organizations (e.g., Climarte, 2017;Julie's Bicycle, 2017). Art can help to concretize scientific data by helping viewers imagine climate change (Corbett & Clark, 2017), and can create personal, emotional connections with viewers (Manzo, 2012;Nurmis, 2016;Roosen, Klöckner, & Swim, 2017;Yusoff & Gabrys, 2011). Also compelling is the potential to reach different and difficult-to-engage audiences (Nurmis, 2016).…”
Section: Art In Digital Mediamentioning
confidence: 99%
“…The past few decades have witnessed artists using images, installations and experiences to communicate about the environment and climate change, with a growing number of eco-Art organizations (e.g., Climarte, 2017;Julie's Bicycle, 2017). Art can help to concretize scientific data by helping viewers imagine climate change (Corbett & Clark, 2017), and can create personal, emotional connections with viewers (Manzo, 2012;Nurmis, 2016;Roosen, Klöckner, & Swim, 2017;Yusoff & Gabrys, 2011). Also compelling is the potential to reach different and difficult-to-engage audiences (Nurmis, 2016).…”
Section: Art In Digital Mediamentioning
confidence: 99%
“…This may be summed up as a reversal of a premise that "art" should act in the service of climate change: for some participants, there was recognition of an opportunity instead for this prominent issue to inform their art, or to make it marketable. In the case of climate change inspiring interesting or provocative art, this has been discussed previously by writers such as Nurmis (2016) who stresses the value of climate change art as "essentially artistic" rather than serving an "instrumental" or activist function, such as promoting action or change in attitudes. Here, the role of the arts may also be conceived as enabling new types of understanding (Gabrys and Yusoff, 2012) or offering different ways of imagining and encountering the environment (Duxbury, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These creative 'interventions' can have a range of aims, including communicating to an audience about environmental issues, raising awareness, reshaping public perceptions, enhancing engagement, and promoting action (Rice et al, 2019). On the topic of climate change, for example, art is often used with a focus on the general public, for communication and awareness raising (Nurmis, 2016) and instigating behavioural change (Burke et al, 2018). In some of these the audience is quite passive, but there are also examples of how the public is engaged in participatory art (Candy et al, 2006).…”
Section: Literature Frameworkmentioning
confidence: 99%
“…Recent review articles on the use of different art-based methods in environmental and health research found that most artbased research is carried out in the United States, Canada, the United Kingdom and France (Nurmis, 2016;Galafassi et al, 2018;Coemans and Hannes, 2017). Research on arts and health is often also done in Africa (Teti et al, 2018) and water-related creative practice research is concentrated in water-scarce regions in Africa and Australia (Fantini, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation